Manajemen Ketahanan Usaha Kedai Kopi Modern dan Tradisional di Tengah Persaingan dan Tekanan Biaya Operasional - Bima Bima; Surya Adi Nugroho; Tsulis Amiruddin Zahri (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the operational management practices of modern and traditional coffee shop MSMEs in responding to increasing business competition and operational cost pressures. The research gap lies in the limited comparative studies examining how key operational practices—particularly cost control, quality consistency, and operational flexibility—are applied by modern and traditional coffee shops. This study employs a qualitative descriptive approach using in-depth interviews with managers of modern coffee shops and traditional coffee stalls in Pangkalpinang City. Data were analyzed through data reduction, thematic coding, and interpretative analysis, focusing on operations management and management accounting perspectives. The findings show that modern coffee shops implement adaptive operational practices by emphasizing product and service quality control, operational flexibility in responding to changing customer demand, and the use of social media as part of operational activities. Traditional coffee shops prioritize operational efficiency through price stability, consistency in production processes, and experience-based cost control developed through long-standing business practices. Although financial recording systems remain relatively simple, both types of businesses demonstrate the ability to sustain operational performance by aligning operational strategies with market characteristics and resource limitations. Context-based operations management approaches in strengthening the resilience of coffee shop MSMEs.